Italy's excellence in research - Rosaria Ciriminna; Cristina Della Pina; Mario Pagliaro (Heliyon)
We analyze excellence in research carried out in Italy using the Highly Ranked Scholars (HRS) ranking of the top 0.05 % of all >30 million scholars. Published by research database ScholarGPS, the ranking is based on classification of over 140 million scholarly publications (weighting each publication and citation by the number of authors, and excluding self-citations). We investigate the outcomes of both prior five-year (2018–2022) and lifetime rankings. Results are informative in many aspects, including in comparison to other nations. The critical analysis of the results may inform policy efforts aimed at opening up a positive long-term economic development perspective for Italy. The analysis may also inform research policy efforts in other countries aimed at connecting research with economic and societal development.